The Impact of Relationships With Government Offices in Entrepreneurial Orientation (Innovative, Proactive) (A Field Study: Syrian Private Banks) (Journal of Hama University, 2019)
The aim of this study is to demonstrate the impact of the network of relations with government offices on the entrepreneurial orientation ( innovative and proactive) by clarifying the concepts related to the network of relations with government offices as part of the structural social capital ,and its role in providing the resources and knowledge required for the innovative orientation And proactive orientation.To achieve the objective of the study is based on the descriptive approach and the design of a questionnaire is distributed to the members of the board of directors and executive management and managers of branches and their deputies in some Syrian private banks,The number of questionnaires distributed is (258), just (159) questionnaires are recovered for analysis.Several international studies have been used to measure independent and dependent variables,that is ,relationships with government offices through three questions, innovative orientation, and proactive orientation as dependent variables using three questions for each variable.The study finds that relations with government offices have a significant impact in innovative orientation, and that relations with government offices influence the proactive orientation significantly. Relations with government offices Support organizations by providing the resources and knowledge, that help them achieve an innovative and proactive orientation.